A biomass-derived super-flexible hierarchically porous carbon film electrode prepared via environment-friendly ice-microcrystal pore-forming for supercapacitors. Issue 73 (13th August 2020) - Ying, Zongrong; Zhang, Yongzheng; Lin, Xuemei; Hui, Shengjie; Wang, Yuxuan; Yang, Yibei; Li, Yuchun
Abstract : An efficient environmentally friendly ice-microcrystal pore-forming strategy utilizing N -methylmorpholine-N-oxide was developed to prepare a biomass-based super-flexible carbon film electrode. Abstract : An efficient environmentally friendly purely-physical ice-microcrystal pore-forming strategy, consisting of three steps including the water-swelling biomass process utilizing N -methylmorpholine-N-oxide, freeze-drying and one-step carbonization, was developed to prepare a biomass-derived super-flexible high-performance carbon film electrode capable of being repeatedly folded.